Virtual reality for pain reduction during intravenous injection in pediatrics: a systematic review and meta-analysis of controlled clinical trials - Ensiyeh Jenabi; Saeid Bashirian; Amir Mohammad Salehi; Masoud Rafiee; Mozhdeh Bashirian (The Korean Pediatric Society, 2023)
Background Intravenous (IV) injections often cause pain, fear, and anxiety in pediatric patients. Virtual reality (VR) is a relatively new intervention that can be used to provide a distraction during or prepare patients for IV injections. Purpose To date, no meta-analysis has examined the evidence regarding the effectiveness of VR at reducing pain in pediatric IV injections. Methods The PubMed, Web of Science, Scopus, and Cochrane Central Register of Controlled Trials databases were searched for articles published through August 7, 2022. The methodological quality of the studies was measured using the Delphi checklist. The chi-square test and the I2 statistic were used to assess heterogeneity across studies. A summary measure of the mean difference in pain scores between the VR and control groups was obtained using a random effects model. All statistical analyses were set at a significance level of 0.05 using Stata 14. Results Nine studies were included in this meta-analysis of VR interventions used during IV injections in pediatric patients. The difference in mean pain score between the intervention and control groups showed significant reductions in the VR group (mean difference, 0.47; 95% confidence interval, 0.3-0.65; I2=9.1%). No interstudy heterogeneity was observed. Conclusion Our results suggest that VR effectively reduces pain associated with IV injections in pediatric patients. No interstudy heterogeneity was noted among the analyzed studies. The Delphi checklist was used to assess methodological quality.